Can flexicurity make ethical sense? The 'terceisation function' as a moral lever for inter-organisational employment schemes. (1st January 2012) - Xhauflair, Virginie; Pichault, François
An employers' alliance (EA) is a group of employers who team up to hire and share workers. It is presented as 'flexicurity in action', in other words, as a tool allowing employers and workers to find new win-win compromises at the company level. Even when motivated by the best of intentions and with all pre-conditions fulfilled, implementing such a new inter-organisational employment scheme might end in failure. We will describe such a failure with the help of a case study showing how employers considered the EA scheme as a possible solution for the informal multi-activity of their staff. We then explore some of the reasons for the failure in implementation and describe how a supporting third party function, which we call the terceisation function, could help the process to succeed and the EA to evolve towards a more equitable and sustainable flexicurity scheme.